2021
DOI: 10.3390/cancers13195014
|View full text |Cite
|
Sign up to set email alerts
|

EZH2 Inhibition as New Epigenetic Treatment Option for Pancreatic Neuroendocrine Neoplasms (PanNENs)

Abstract: Pancreatic neuroendocrine neoplasms are epigenetically driven tumors, but therapies against underlying epigenetic drivers are currently not available in the clinical practice. We aimed to investigate EZH2 (Enhancer of Zest homolog) expression in PanNEN and the impact of EZH2 inhibition in three different PanNEN preclinical models. EZH2 expression in PanNEN patient samples (n = 172) was assessed by immunohistochemistry and correlated with clinico-pathological data. Viability of PanNEN cell lines treated with EZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…These cell type-specific differences might be explained by the fact that DZNep affects global, not EZH2-specific histone methylation by inhibiting the S-adenosyl-homocysteine hydrolase, which leads to the accumulation of the inhibitory S-adenosyl-homocysteine with broad effects on different cellular pathways [ 69 , 73 ]. In line with our findings, a recent report using a different EZH2 inhibitor, GSK126, showed significant antitumoral effects induced by EZH2 inhibition both in vitro and in a murine model of pancreatic neuroendocrine tumorigenesis [ 74 ].…”
Section: Discussionsupporting
confidence: 91%
“…These cell type-specific differences might be explained by the fact that DZNep affects global, not EZH2-specific histone methylation by inhibiting the S-adenosyl-homocysteine hydrolase, which leads to the accumulation of the inhibitory S-adenosyl-homocysteine with broad effects on different cellular pathways [ 69 , 73 ]. In line with our findings, a recent report using a different EZH2 inhibitor, GSK126, showed significant antitumoral effects induced by EZH2 inhibition both in vitro and in a murine model of pancreatic neuroendocrine tumorigenesis [ 74 ].…”
Section: Discussionsupporting
confidence: 91%
“…For primary cell isolation, micro-cell block manufacture, and quantification, we followed the workflow described previously. 14 In this study of high-grade GEP-NENs and in our earlier studies of lower-grade PanNENs 14,17 , our definition of "culture success" for patient-derived tumoroids was based on six factors that support translational application of patient-derived GEP-NEN tumoroids: 1) Successfully isolating and culturing viable tumor cells; 2) retaining ± 70% of the isolated cells before drug screening; 3) passing quality controls, including cytological, morphological, and histopathological examinations of clinically applied neuroendocrine marker expression in micro-cellblocks; 4) attaining sufficient technical replicates (n≥4) in drug screenings; 5) attaining stable RTG baseline and cell growth; 6) and extending culture life spans of up to 12 days ex vivo.…”
Section: Primary and Cell Line Culturementioning
confidence: 71%
“…The development of neuroendocrine prostate cancer seems to be mediated by EZH2 [ 50 , 51 ]. Furthermore, several preclinical studies have demonstrated that direct or indirect targeting of EZH2 is a potential new therapeutic strategy for NEN of the pancreas and small intestine [ 32 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, PRC2-independent functions of EZH2, e.g., the modification of protein activity by methylation or direct binding, have also been described in different cancer entities [ 25 , 26 , 27 , 28 , 29 , 30 ]. EZH2-mediated gene-silencing and other epigenetic mechanisms in cancer development and progression have gained increasing interest and offer new treatment options [ 19 , 31 , 32 ]. In most cancer entities (e.g., pancreatic cancer, breast cancer, prostate cancer, lung cancer), EZH2 is clearly associated with pro-tumorigenic and tumor-progressive characteristics [ 33 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%